1999
DOI: 10.1111/j.1699-0463.1999.tb01510.x
|View full text |Cite
|
Sign up to set email alerts
|

Serological response to Helicobacter pylori recombinant antigens in Chilean infected patients with duodenal ulcer, non‐ulcer dyspepsia and gastric cancer

Abstract: A. Serological response to Helicobacter pylori recombinant antigens in Chilean infected patients with duodenal ulcer, non-ulcer dyspepsia and gastric cancer. APMIS 1999; 107: 1069-78.We have previously cloned 10 Helicobacter pylori antigen genes from a Chilean strain including: cytotoxin VacA, a truncated region of CagA (called A17), a species-specific protein (Ag26), urease subunits (UreA, UreB), a flagellin, (FlaB), heat shock proteins (HspA and HspB), an adhesin (HpaA) and a lipoprotein (Lpp20). Immunogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…The FlaA and FlaB expressed by H pylori rendered the organism strong motility in mucous environment, induced IL-8 secretion and facilitated inflammation in gastric tissue [51,52] . Furthermore, we observed that serum antibodies against FlaA and FlaB were present in approximate 98.4 % and 92.8 % of H pylori infected patients, respectively, the rates were significantly higher than those of heat shock protein (68 %) and vacuolating cytotoxin (68 %) [60] . These data indicate that flaA and flaB genes express their products in majority of H pylori strains and efficiently induce specific antibodies, implying a brilliant potential for developing H pylori vaccine.…”
Section: Elisamentioning
confidence: 79%
“…The FlaA and FlaB expressed by H pylori rendered the organism strong motility in mucous environment, induced IL-8 secretion and facilitated inflammation in gastric tissue [51,52] . Furthermore, we observed that serum antibodies against FlaA and FlaB were present in approximate 98.4 % and 92.8 % of H pylori infected patients, respectively, the rates were significantly higher than those of heat shock protein (68 %) and vacuolating cytotoxin (68 %) [60] . These data indicate that flaA and flaB genes express their products in majority of H pylori strains and efficiently induce specific antibodies, implying a brilliant potential for developing H pylori vaccine.…”
Section: Elisamentioning
confidence: 79%
“…HpaA gene is located in genome DNA of H.pylori and considerably conservative for its nucleotide and amino acid sequences [55,56] . Furthermore, antibody against HpaA could be found in approximately 86 % of H.pylori infected patients' sera and this proportion was obviously higher than that of heat shock protein (68 %) and vacuolating cytotoxin (68 %) [57] and was similar to that of urease B [64] . Therefore, HpaA is an ideal antigen candidate for H.pylori vaccine.…”
Section: Discussionmentioning
confidence: 90%
“…The result of ELISA for an H.pylori ultrasonic supernatant was considered as positive if its OD 490 value was over the mean plus 3 SD of 6 cases of ultrasonic supernatant at the same protein concentration of E.coli ATCC 25922 played as negative control [54] . Data analysis The nucleotide sequences of the cloned hpaA gene inserted in the two recombinant plasmid vectors were compared for homologies with 6 published hpaA gene sequences (X92502, NC000915, X61574, NC000921, AF479028 and U35455) [51,53,[55][56][57][58] with a special molecular biological analysis soft ware.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some reports provide evidence for the usefulness of the immunoblotting diagnosis of GDU in Brazilian children (25). Other authors claim that there is no association of specific H. pylori antigens with antibodies in adult patients suffering from various gastroduodenal pathologies in Germany (14) and Chile (20). Apparently, these contradictory findings reflect both the phenotypic heterogeneity of H. pylori and the specificity of the host immune response within various populations.…”
Section: Vol 40 2002 Novel H Pylori Antigens 549mentioning
confidence: 99%